ANALYSIS OF FACTORS AFFECTING COMPANY VALUE WITH MANAGERIAL OWNERSHIP AS MODERATING VARIABLES LISTED ON THE INDONESIA STOCK EXCHANGE FOR THE 2012-2015 PERIOD - Sriayu Saputri Situmeang; Rina Bukit; Tapi Anda Sari Lubis (CV. Radja Publika, 2023)
This study aims to determine the analysis of the factors that influence the value of companies with managerial ownership as a moderating variable in manufacturing companies listed on the Indonesia Stock Exchange for the 2012-2015 period. This research is a research with a causal associative approach. The method of determining the sample for this study is the proportional stratified random sampling method, namely the population is grouped according to the type of industrial sector. From each of these groups, a number of samples were determined proportionally and selected randomly. The results of the study show that simultaneously the variables Leverage, Profitability, Company Size and Investment Opportunity Set have an effect on Firm Value in manufacturing companies listed on the IDX for the period 2012 – 2014,